Current and Potential Applications of Atmospheric Cold Plasma in the Food Industry - Darin Khumsupan; Shin-Ping Lin; Chang-Wei Hsieh; Shella Permatasari Santoso; Yu-Jou Chou; Kuan-Chen Hsieh; Hui-Wen Lin; Yuwen Ting; Kuan-Chen Cheng (Molecules, 2023)
The cost-effectiveness and high efficiency of atmospheric cold plasma (ACP) incentivise researchers to explore its potentials within the food industry. Presently, the destructive nature of this nonthermal technology can be utilised to inactivate foodborne pathogens, enzymatic ripening, food allergens, and pesticides. However, by adjusting its parameters, ACP can also be employed in other novel applications including food modification, drying pre-treatment, nutrient extraction, active packaging, and food waste processing. Relevant studies were conducted to investigate the impacts of ACP and posit that reactive oxygen and nitrogen species (RONS) play the principal roles in achieving the set objectives. In this review article, operations of ACP to achieve desired results are discussed. Moreover, the recent progress of ACP in food processing and safety within the past decade is summarised while current challenges as well as its future outlook are proposed.